PERAN KEPEMIMPINAN TRANSFORMASIONAL KEPALA SEKOLAH BERLANDASKAN SISTEM AMONG DALAM MENINGKATKAN MUTU PEMBELAJARAN DI SDN 03 SURU KAB. PEMALANG - Saparudin, Eko; Dina Hikmah Safariyah; Soedjono (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
School culture management plays a crucial role in creating a conducive learning environment. This study aims to analyze the strategies of school principals in implementing effective school culture management at SD Negeri 02 Sukorejo, Pemalang Regency. Using a qualitative method with a descriptive approach, data was collected through interviews, observations, and document studies. The results indicate that the principal plays a key role in building a positive culture by strengthening shared values, engaging the school community, and implementing programs that support the school's vision and mission. Cultural programs such as "Jabat Tangan" and "BERJUMPA" are designed participatively, involving all school members. The principal’s strategies ensure that local values endure and remain relevant amidst the challenges of globalization. The conclusion of this study emphasizes that collaborative and innovative leadership from the principal is crucial to creating an effective school culture.